Exopolysaccharide (EPS) activity test of lactic acid bacteria (LAB) as immunomodulatory - Kusmiati .; Fifi Afiati; Farha Elein Kukihi (Jurnal Ilmu Ternak dan Veteriner, 2016)
Immunomodulatory activity assay and characterization of exopolysaccharide (EPS) from Lactic Acid Bacteria (LAB) was done in Bogor. Bacteria used in this study was LAB strains of Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus. Exopolysaccharide was extracted from L. delbrueckii subsp. bulgaricus and S. thermophilus then characterized with FT-IR spectrophotometer to determine the functional group. IR spectrum analysis using Fourier Transform-Infra Red (FT-IR) showed that EPS from both LAB isolates were carbohydrate compounds. Immunomodulatory activity in vivo from EPS was measured using phagocytic activity and phagocytic capacity macrophage cells from mice peritoneal cavity fluid. Exopolysaccharide were given orally to mice in concentrations of 100 μg/ml, 200 μg/ml and 300 μg/ml for 14 days then the mice were infected with Staphylococcus aureus. Result showed that EPS from both LAB isolate enhanced either phagocytic activity and phagocytic capacity macrophage cell from mice peritoneal fluid. EPS from L. delbrueckii subsp. bulgaricus concentration 300 μg/ml showed the highest phagocytic activity of macrophage cells and EPS from S. thermophilus concentration 300 μg/ml showed the highest phagocytic capacity. It is concluded that EPS potency tested as immunomodulatory derived from a culture of L. delbrueckii and S. thermophilus subsp.bulgaricus are able to increase the activity and phagocytosis murine peritoneal macrophages.